Pengaruh Tingkat Pendidikan dan Status Pekerjaan terhadap Pemilihan Produk Skincare di Kabupaten Mojokerto - Reza Amilia Febriana; Nia Kusstianti; Maspiyah; Dewi Lutfiati (Jurnal Tata Rias, 2026)
The use of skincare products has increased alongside growing public awareness regarding the importance of maintaining skin health. This study aims to: (1) describe the characteristics of skincare product consumers in Mojokerto Regency; (2) determine the influence of education level on product choice; (3) understand the influence of employment status on product choice; and (4) determine the joint influence of education level and employment status on product choice. The study employs a quantitative approach based on a correlational research method. The sample consists of 116 respondents, all of whom are skincare product users in Mojokerto Regency. Data were collected via questionnaires and subsequently analyzed using validity and reliability tests, multiple linear regression, classical assumption tests, the coefficient of determination, t-tests, and F-tests, utilizing IBM SPSS Statistics 26 software. The results indicate that education level exerts a significant influence on the choice of skincare products (significance value of 0.000), whereas employment status does not have a significant influence (significance value of 0.153). Based on these findings, it can be concluded that education level has a significant partial effect on product choice, unlike employment status. However, education level and employment status exert a significant joint influence on the choice of skincare products in Mojokerto Regency.